Pharmacodynamic Effect of mTOR Inhibition-based Immunosuppressive Therapy on T- and B-cell Subsets After Renal Transplantation - Wei, Xinyi; Weber, Sabine; Yin, Decheng; Allabauer, Ida; Jobst-Schwan, Tilman; Wiesener, Michael; Schiffer, Mario; Dudziak, Diana; Lehmann, Christian; Wölfle, Joachim; Hörning, André (Transplantation Direct, 2024)
Background. The mammalian target of rapamycin inhibitor (mTORi) therapy after kidney transplantation is solely monitored pharmacokinetically, not necessarily reflecting PI3K-Akt-mTOR pathway blockade efficacy leading to potential under- or overimmunosuppression. Methods. In this cross-sectional study, phosphoflow cytometry was used to determine the efficacy of mTOR inhibition in peripheral T- and B-lymphocyte subsets by assessing p70S6 kinase (p70S6K) phosphorylation in renal transplant recipients upon treatment with a combination of either mTORi and calcineurin inhibitors (n = 18), or mTORi with mycophenolic acid (n = 9). Nine dialysis patients with end-stage renal disease and 17 healthy age-matched volunteers served as controls. Results. mTORi treatment reduced p70S6K phosphorylation in CD4+, CD8+ T, and CD19+ B cells compared with healthy controls (HCs). Subpopulation analysis of CD4+ T cells and CD19+ B cells revealed a significant reduction of p70S6K phosphorylation in CD4+CD45RA−CD25− Th cells (P < 0.05), CD24hiCD38hi transitional B cells (P < 0.001), CD24+CD38− memory B cells (P < 0.001), and CD24intCD38int-naive B cells (P < 0.05) upon mTORi treatment, whereas CD4+CD45RA−CD25++CD127− regulatory T cells and CD24−CD38hi plasmablasts were not affected. Compared with mTORi + mycophenolic acid therapy, mTORi + calcineurin inhibitor treatment exhibited an even stronger inhibition of p70S6K phosphorylation in CD4+CD45RA−CD25− Th cells and CD8+ T cells. However, trough levels of mTORi did not correlate with p70S6K phosphorylation. Conclusions. mTORi selectively inhibited p70S6K phosphorylation in select lymphocyte subtypes. Assessing p70S6K phosphorylation by phosphoflow cytometry may serve as an approach to understand cell subset specific effects of mTORi providing detailed pharmacodynamic information for individualizing immunosuppression.
CRIS-Team Scopus Importer:2024-07-19